Trichoderma‐Derived Pentapeptides from the Infected Nest Mycobiome of the Subterranean Termite Coptotermes testaceus. (1st April 2022) - Oberpaul, Markus; Brinkmann, Stephan; Spohn, Marius S.; Mihajlovic, Sanja; Marner, Michael; Patras, Maria A.; Toti, Luigi; Kurz, Michael; Hammann, Peter E.; Vilcinskas, Andreas; Glaeser, Jens; Schäberle, Till F.
Abstract: Termites live in a dynamic environment where colony health is strongly influenced by surrounding microbes. However, little is known about the mycobiomes of lower termites and their nests, and how these change in response to disease. Here we compared the individual and nest mycobiomes of a healthy subterranean termite colony ( Coptotermes testaceus ) to one infected and ultimately eradicated by a fungal pathogen. We identified Trichoderma species in the materials of both nests, but they were also abundant in the infected termites. Methanolic extracts of Trichoderma sp. FHG000531, isolated from the infected nest, were screened for secondary metabolites by UHPLC‐HR MS/MS‐guided molecular networking. We identified many bioactive compounds with potential roles in the eradication of the infected colony, as well as a cluster of six unknown peptides. The novel peptide FE011 was isolated and characterized by NMR spectroscopy. The function of this novel peptide family as well as the role of Trichoderma species in dying termite colonies therefore requires further investigation. Abstract : Metabolic opportunities from an infected termite nest : Isolation and structural analysis by NMR spectroscopy and MS/MS revealed a novel pentapeptide (FE011) and five derivatives produced by a strain of Trichoderma enriched in and isolated from an infected nest of the wood‐feeding termite Coptotermes testaceus .